Dose Analysis of Gadolinium Neutron Capture Therapy (GdNCT) on Cancer Using SHIELD-HIT12A - Bagus Novrianto Fasni; Yohannes Sardjono; Boni Pahlanop Lapanporo (Universitas Gadjah Mada, 2018)
This research aimed to determine the dose of radiation received in cancer therapy for each decay of Gadolinium atomic nuclei with isotope 157 (157Gd) in Gadolinium Neutron Capture Therapy using the SHIELD-HIT12A program. Knowing the amount of dose given to cancer tissue should aid in minimizing the damage that could occur in the healthy tissue around the cancer tissue, effectively killing only the cancer cells. The simulation employed in this research used the SHIELD-HIT12A program by providing input on beam.dat, mat.dat, detect.dat, and geo.dat files. The output data from the program comprised the value of recoil energy lost (energy absorbed into the target materials) for each of the 157Gd atomic nuclei, which was then processed by the dose determination equation to determine the dose given by the 157Gd nucleus to soft tissue. Based on the results, the amount of the dose given by each atomic nucleus 157Gd to soft tissue was 5.44 × 1011 Gy/decay.